A REVIEW AND CONCEPTUALIZATION FOR SOCIAL COLLABORATION ACHIEVEMENT IN BIM CONSTRUCTION CONTEXT - Raja Mohd Noor, Raja Nor Husna; Che Ibrahim, Che Khairil Izam; Belayutham, Sheila (Journal of Surveying, Construction and Property, 2020)
The emergence of widespread advanced digital technologies being utilised into the construction industry practices adds a new dimension to the better integration and collaboration of construction projects. Nowadays, Building Information Modelling (BIM) is recognized as a modern tool to enhance greater visualisation of project information and provides opportunities for an effective communication platform within a multi-organisations context. Despite the wave of enthusiasm for BIM studies having shown exceptional benefits, the context of social collaboration across multi-organisations is still limited. Thus, this paper aims to present the review of key indicators towards social collaboration achievement within multi-organisations in the BIM construction context. Based on a comprehensive review, five key indicators are identified that contribute to the social collaboration achievement in BIM construction context. Including organisational perspectives, foundational setting, behavioural perspective, educational perspective and enforcement platform. The findings also revealed the extend of the spectrum of collaboration literature in the context of construction domain particularly on characterisation and its importance towards social collaboration within a multi-organisation in digital environment.